UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAN FRAKSI Archidendron clypearia TERHADAP Staphylococcus aureus dan Salmonella typhi : ANTIBACTERIAL ACTIVITY TEST OF ETANOL EXTRACT AND FRACTIONS OF Archidendron clypearia OF Staphylococcus aureus and Salmonella typhi - Octaviani, Bella Micha Thesya; Fahmi, Supomo; Syamsul, Eka Siswanto (JFL : Jurnal Farmasi Lampung, 2025)
Infection is one of the most common causes of disease in society. One type of infection caused by Staphylococcus aureus is a bacterium that causes skin infections in humans characterized by purulent abscesses. In addition, Salmonella typhi is also a pathogenic bacterium that can cause typhoid fever. Infections caused by microorganisms can be overcome by administering antimicrobials. One of the natural ingredients that has the potential as an antimicrobial is the petai belalang plant (Archidendron clypearia). This study aims to test the antibacterial activity of ethanol extracts and fractions of petai belalang leaves against Staphylococcus aureus and Salmonella typhi bacteria. This experimental research includes plants determination, sampling, making simplisia, fractionation, phytochemical screening, and antibacterial activity tests. Extracts and fractions were prepared in concentrations of 1%, 5%, 10%, and 15%, with positive control of amoxicillin 0.1% and negative control of DMSO 1%. The antibacterial activity test was performed using disc diffusion and pitting diffusion methods to measure the zone of inhibition. Data were statistically analyzed using the Kruskal-Wallis test. The results showed that in the disc diffusion method, the inhibition zone against Staphylococcus aureus was 7.3-10.8 mm, and against Salmonella typhi was 7.6-10.1 mm. In the well diffusion method, the zone of inhibition against Staphylococcus aureus ranged from 12.1-16.8 mm, and against Salmonella typhi it ranged from 12.5-16.8 mm. The ethyl acetate fraction obtained the largest inhibition zone with a diameter of 16.8 mm in the well diffusion method. Statistical analysis showed a significant difference in antibacterial activity on positive and negative bacteria with a substantial value of 0.005 in the disc method and 0.006 in the well method. Keywords: Antibacterial, petai belalang, Staphylococcus aureus, Salmonella typhi